A Family Focused Intervention Influences Hippocampal‐Prefrontal Connectivity Through Gains in Self‐Regulation. Issue 4 (8th October 2018) - Hanson, Jamie L.; Gillmore, Alysha D.; Yu, Tianyi; Holmes, Christopher J.; Hallowell, Emily S.; Barton, Allen W.; Beach, Steven R.H.; Galván, Adrianna; MacKillop, James; Windle, Michael; Chen, Edith; Miller, Gregory E.; et al.
Abstract : The stressors associated with poverty increase the risks for externalizing psychopathology; however, specific patterns of neurobiology and higher self‐regulation may buffer against these effects. This study leveraged a randomized control trial, aimed at increasing self‐regulation at ~11 years of age. As adults, these same individuals completed functional MRI scanning ( M age  = 24.88 years; intervention n  = 44; control n  = 49). Functional connectivity between the hippocampus and ventromedial prefrontal cortex was examined in relation to the intervention, gains in self‐regulation, and present‐day externalizing symptoms. Increased connectivity between these brain areas was noted in the intervention group compared to controls. Furthermore, individual gains in self‐regulation, instilled by the intervention, statistically explained this brain difference. These results begin to connect neurobiological and psychosocial markers of risk and resiliency.